Cost-effectiveness of golimumab for the treatment of patients with moderate-to-severe ulcerative colitis in Quebec using a patient level state transition microsimulation. (2nd January 2018) - Stern, Sean; Ward, Alexandra J.; Saint-Laurent Thibault, Catherine; Camacho, Fernando; Rahme, Elham; Naessens, Dominik; Aumais, Guy; Bernard, Edmond-Jean; Bourdages, Raymond; Cohen, Albert; Pare, Pierre; Dyrda, Peter
Abstract: Objective: To conduct cost-effectiveness analyses comparing the addition of golimumab to the standard of care (SoC) for treatment of patients with moderate-to-severe ulcerative colitis (UC) who are refractory to conventional therapies in Quebec (Canada). Methods: An individual patient state transition microsimulation model was developed to project health outcomes and costs over 10 years, using a payer perspective. The incremental benefit estimates for golimumab were driven by induction response and risk of a flare. Flare risks post-induction were derived for golimumab from the PURSUIT maintenance trial and extension study, while those for SoC were derived from the placebo arms of the Active Ulcerative Colitis Trials (ACT) 1 and 2. Other inputs were derived from multiple sources, including retrospective claims analyses and literature. Costs are reported in 2014 Canadian dollars. A 5% annual discount rate was applied to costs and quality-adjusted life-years (QALYs). Results: Compared with SoC, golimumab was projected to increase the time spent in mild disease or remission states, decrease flare rates, and increase QALYs. These gains were achieved with higher direct medical costs. The incremental cost-effectiveness ratio for golimumab vs SoC was 63, 487 per QALY. Limitations: The long-term flare projections for SoC were based on the data available from the ACT 1 and 2 placebo arms, as data were not available from the PURSUIT maintenance or extension trial. Additionally, the study was limited to only SoC and golimumab, due to the availability of individual patient data to analyze. Conclusion: This economic analysis concluded that treatment with golimumab is likely more cost-effective vs SoC when considering cost-effectiveness acceptability thresholds from 50, 000–100, 000 per QALY.